Integrated process for extraction and purification of alcohol dehydrogenase from Baker's yeast involving precipitation and aqueous two phase extraction - Madhusudhan, M. C.; Raghavarao, K. S. M. S.; Nene, Sanjay (Biochemical Engineering Journal, 2008)
The potential of aqueous two phase extraction for the purification of alcohol dehydrogenase (ADH) from Baker's yeast (Saccharomyces cerevisiae) is demonstrated. An integrated process involving precipitation followed by aqueous two phase extraction (ATPE) is used for effective recovery of the enzyme. This is carried out in two schemes. In the first scheme, ammonium sulphate precipitation is carried out followed by ATPE of the precipitate after suspending it in buffer. While the second scheme involves polyethylene glycol precipitation followed by ATPE of the supernatant. The effect of various process parameters such as molecular weight of polymer, tie line length, phase volume ratio and neutral salt is investigated for enhancing the activity recovery of ADH. First scheme resulted in about 85% enzyme activity recovery of ADH with purification factor of 4.2 while the second scheme about 90% enzyme activity recovery with 6.6-fold purification. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Alcohol dehydrogenase; aqueous two phase extraction; enzyme extraction; Precipitation; Purification; Yeast